From evidence to national scale: An implementation framework for micronutrient powders in Rwanda - McLean, Judy (Matern Child Nutr, 2018)
Micronutrient powders (MNP) are an efficacious intervention in terms of reducing anaemia among young children, yet challenges remain regarding implementation at scale. Research that can guide effective implementation of nutrition interventions and facilitate integration into existing health care platforms is needed. This paper seeks to advance the implementation science knowledge base by presenting our multiphased strategy and findings for scaling‐up MNP in Rwanda. The multiphased implementation strategy, spanning a 5‐year period (2011–2016), included (a) a feasibility study involving formative research, (b) a 30‐day trial of improved practices (n = 60 households), (c) a 12‐month pilot that included an effectiveness study (n = 1,066 caregiver/child pairs), and (d) a staggered approach to national scale‐up. At the end of Phase 4, the programme had been implemented in 19 of Rwanda's 30 districts with the scale‐up in the final 11 districts completed in the following year. The caregivers of over 270,000 eligible children 6–23 months of age received a box of 30 MNP sachets in the final 3‐month assessment period, representing a coverage rate of 87%. Initial problems with the supply chain and distribution and ongoing challenges to monitoring and reporting have been the largest obstacles. Continued success will be dependent on adequate resources for capacity development, refresher training, and responsive monitoring. Rwanda is one of the first countries to successfully scale‐up home fortification subnationally with MNP. Lessons learned have implications for other countries.